THE ROLE OF GREEN PERCEIVED VALUE AND INNOVATION IN SMALL AND MEDIUM ENTERPRISES COMPETITIVENESS - Hayati Nupus; Wawan Ichwanudin; Assas Worasutr (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
This study aims to examine the impact of Green Marketing on Small and Medium Enterprises (SMEs) Competitiveness by investigating the role of Green Perceived Value as a mediator and Green Innovation as a moderator. Using a survey design, quantitative data were collected from 97 owners and managers of SMEs in Serang who implement green practices and analyzed using the SEM-PLS method. The results show that Green Marketing does not have a significant direct impact on SMEs Competitiveness. However, Green Marketing significantly increases consumers' Green Perceived Value, which fully mediates the relationship between Green Marketing and SMEs Competitiveness. This finding emphasizes that the effectiveness of green strategies largely depends on how consumers evaluate and respond to the products. Additionally, Green Innovation acts as a moderator, strengthening the positive impact of Green Perceived Value on SMEs Competitiveness. Therefore, to achieve sustainable competitive advantage, Green Marketing must be integrated with innovations that enhance value in consumers' eyes, thereby delivering greater impact for SMEs.